Prospective study of uterine corpus lesions over a period of one year in tertiary care centre - Chandralekha, Janagam; Sumanlatha, Guntur Roda; Kartheek, Botta Venkata Satya; Bhagyalakshmi, Atla (International Journal of Research in Medical Sciences, 2017)
Background:Hysterectomy is the most commonly performed gynaecological surgery throughout the world. Few studies have been performed describing the pathologic findings in hysterectomy specimens and examining the relationship between the preoperative clinical indication, gross findings and pathologic diagnosis. This study was undertaken to identify the different types of pathologies in hysterectomy specimens and to correlate the findings with the clinical indications and gross findings. Methods: In the present study, five hundred and forty four cases were studied over a period of one year. Surgical specimens were formalin fixed and the tissue was adequately processed for histopathological examination. The sections were stained routinely with hematoxylin and eosin stain. Results: Menorrhagia and fibroid uterus were the most common clinical indications for hysterectomy. Of the 544 cases, 52.75% cases were encountered in the age group of 40 - 49 years which was the most common age group. The most common pathology identified was leiomyoma in myometrium. Histopathological examination confirmed the clinical and gross diagnosis in majority of the cases. Conclusions: The present study provides a fair insight into the histological patterns of lesions in hysterectomy specimens in our institution. A wide range of lesions are encountered when hysterectomy specimens are subjected to histopathological examination. Though the histopathological analysis correlates well with the clinical and gross diagnoses, a few lesions were also encountered as incidental findings and mismatch diagnoses. Hence, it is mandatory that every hysterectomy specimen should be subjected to detailed gross and histopathological examination to ensure proper postoperative management of patients.